The Impediments to Effective Community Policing in Nigeria: A Case Study of Akwa Ibom State (Global Journal of Human-Social Science, 2020)
Community policing is a philosophy of full-service personalized policing, where the same officer patrols, and works in the same area permanently from a decentralized place, working in a proactive partnership with citizens to identify and solve problems. It is established at the bedrock of police-community partnership and communication to secure a safe environment for all and develop a longer-term solution to resolving criminal issues. The objective of this study was to assess the impediments against operative community policing in crime prevention with unusual reference to Akwa Ibom State. The theories use for this research were the democratic theory of community policing. The research adopted a Chi-Square analytical method for a statistical analysis questionnaire that was used6 for data collection from participants from 4 selected study areas -Ikot Abasi, Oron, Uyo, and Ikot Ekpene.
Keywords: community policing; crime prevention; police and policing; crime